BAHASA MASUK PORTUGIS KURIKULUM DALAM PEMBERITAAN DI MEDIA MASSA: ANALISI WACANA KRITIS - Rully Sulistyawan P.A; Cindy Angelina Putri Tambunan; Mazaya Elya Sakinah (CV. Denasya Smart Publisher, 2026)
This research aims to uncover the representation of power and ideology in media coverage regarding educational policy. The focus of the study is directed at a news article from Kompas.com titled